EVALUASI NILAI CUTTING CARRYING INDEX PADA LUMPUR DIESEL OIL - Kevin Ariko Yuwandhika; Bayu Satiyawira; Apriyandi Rizki (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2018)
Evaluation of Cutting Carrying Index when using Diesel Oil base mud in well T is carried out on section 12-1 / 4 ", 8-1 / 2", and 5-3/4 ". This is because the use of mud on the previous section did not use Diesel Oil base mud, but only used native mud and KCL Polymer base mud. In the CCI evaluation of the Diesel Oil mud, several parameters included, Equivalent Circulating Density and rheology of diesel oil base mud. Based on the primary data on well T the ECD calculation can be done by calculating the average annulus velocity, velocity critical around annulus hole, and the  pressure loss in it. The value of ECD obtained on section 12-1 / 4 "ranges from 14 ppg to 15 ppg, section  8-1/2”  has 16,08 ppg to 16,4 ppg, and section 5-3 / 4" reaching 14,72 ppg as the biggest value. Based on the ECD, CCI value is obtained, this is because the ECD value describes the mud weight around the annulus hole. A good CCI value must be greater than or equal to 1, then evaluated with the results of CCI on route 12-1 / 4 "obtaining the greatest CCI value 1.6 in the jar and drill collar I. On route 8-1 / 2", CCI value evaluated in the heavyweight drill pipe section with a change in the value of 0,76 to 1,08. The CCI value on section 5-3 / 4“ changes in value from 0,65 to 1,19 in heavyweight drill pipe section.